A prospective randomized control trial of topical tranexamic acid used in elderly patients with femoral neck fractures treated with hemiarthroplasty - K. P., Pruthvi; Meena, Ramesh Chandra; Rayanad, Mallikarjun K. (International Journal of Research in Orthopaedics, 2023)
Background: Geriatric hip fracture patients frequently suffer femoral neck injuries. The advantage of using TXA topically over the IV route is that maximum concentration of the drug is attained at the wound/surgical site with minimal systemic side effects of drug and also it is easy to administer locally. Aim of current study was fragmented necks of the femur can be treated with Tranexamic acid to reduce postoperative blood loss. Methods: Over the course of 20 months from June 2020 to December 2021, the orthopaedics department at SMS Hospital, Jaipur, conducted this study. A total of 174 patients (87 in each group) of age >60 years, presenting with neck of the femur in orthopaedics wards were enrolled in this study. Results: Compared to the control group, the case group experienced 408 ml more blood loss, which was treated with tranexamic acid. In cases and controls, transfusion was necessary for 31 and 41 patients, respectively. Conclusions: One dosage of topical tranexamic acid may be given to an older patient undergoing bipolar hemiarthroplasty for a fractured femoral neck in order to minimize post-operative blood loss.